2012
DOI: 10.3171/2012.8.spine111003
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of traumatic spinal fractures: experience from medical university–affiliated hospitals in Chongqing, China, 2001–2010

Abstract: Object The main objective of this study was to analyze the epidemiological data obtained from patients with traumatic spinal fracture at 2 university-affiliated hospitals in Chongqing, China. Methods The authors retrospectively reviewed the hospital records of all patients who suffered traumatic spinal fracture and were treated at Xinqiao Hospital and Southwest Hospital (both affiliated with The Third Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
120
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(145 citation statements)
references
References 20 publications
21
120
2
2
Order By: Relevance
“…4,5,7 This range practically coincides with the peak of the economically active population (EAP) in Brazil, which is from 25 to 49 years of age (60.9% of the EAP in 2015). 15 Thus, spinal fractures have a great economic impact, since the group with the highest incidence is exactly that of young economically active individuals.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…4,5,7 This range practically coincides with the peak of the economically active population (EAP) in Brazil, which is from 25 to 49 years of age (60.9% of the EAP in 2015). 15 Thus, spinal fractures have a great economic impact, since the group with the highest incidence is exactly that of young economically active individuals.…”
Section: Discussionmentioning
confidence: 78%
“…In addition, they are mainly associated with traffic accidents and falls from heights. 4,5 The same epidemiological pattern is maintained in patients with spinal cord injuries, with an annual incidence of approximately 19.4 patients per million inhabitants in France, 10.7 in Germany, 38.4 in the USA, and 21.0 in Brazil. [6][7][8] There is dearth of epidemiological studies about spinal fractures in Brazil.…”
Section: Introductionmentioning
confidence: 84%
“…Osteoporotic vertebral fractures may occur without trauma; nonetheless, our results suggest traumatic vertebral fractures are also remarkably frequent in elderly population. Previous studies have reported that vertebral fractures were observed 1.9-3.3-fold more frequent in men than in women 2,4,10,12,13 . Contrary to these results, we found male-to-female ratio as 1.5.…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly, compression and burst fractures are observed after falls, whereas fracturedislocations are most frequently observed after motor vehicle accidents 4,15 . Among all causes of fractures, the incidence rates of falls have been reported to range between 54, and 62% in various studies 2,3,10,13,16 . The fall from a height was observedly the most common cause of trauma at a much higher rate of 79% among patients aged over 65 years who were admitted to the emergency department 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation